Psychological Well-Being and Social Support as Moderators of the Stress Coping–Performance Relationship Among University Students - Uy, Heather Faith B.; Narsico, Peter G.; Estudillo, Joel L.; Delantar, Jinky R.; Narsico, Lalaine O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated whether stress coping skills predict academic performance among university students. Using data from 348 participants, a simple linear regression analysis was conducted. The results showed that stress coping significantly predicted academic performance, with the model explaining 12.4% of the variance (R² = .124). The overall regression was statistically significant, F(1, 346) = 49.00, p < .00001. The coefficient for stress coping was positive and significant (β = 0.184, SE = 0.026, t = 7.00, p < .00001), indicating that for each one-unit increase in coping ability, academic performance increased by 0.184 units on average. The intercept was also significant (β = 2.936, SE = 0.090, t = 32.62, p < .00001), representing the expected academic performance score when coping is at its average level. These findings suggest a meaningful positive relationship between students’ ability to manage stress and their academic outcomes. Students who use effective coping strategies, such as emotional regulation and proactive problem-solving, tend to perform better academically.